Hg isotopic composition of one-year-old spruce shoots: Application to long-term Hg atmospheric monitoring in Germany. (September 2021) - Yamakawa, Akane; Amouroux, David; Tessier, Emmanuel; Bérail, Sylvain; Fettig, Ina; Barre, Julien P.G.; Koschorreck, Jan; Rüdel, Heinz; Donard, Olivier F.X.
Abstract: The Hg isotopic composition of 1-year-old Norway spruce ( Picea abies ) shoots collected from Saarland cornurbation Warndt, Germany, since 1985 by the German Environmental Specimen Bank, were measured for a better understanding of the temporal trends of Hg sources. The isotopic data showed that Hg was mainly taken up as gaseous element mercury (GEM) and underwent oxidation in the spruce needles; this led to a significant decrease in the δ 202 Hg compared with the atmospheric Hg isotopic composition observed for deciduous leaves and epiphytic lichens. Observation of the odd mass-independent isotopic fractionation (MIF) indicated that Δ 199 Hg and Δ 201 Hg were close to but slightly lower than the actual values recorded from the atmospheric measurement of the GEM isotopic composition in non-contaminated sites in U.S. and Europe, whereas observation of the even-MIF indicated almost no differences for Δ 200 Hg. This confirmed that GEM is a major source of Hg accumulation in spruce shoots. Interestingly, the Hg isotopic composition in the spruce shoots did not change very significantly during the study period of >30 years, even as the Hg concentration decreased significantly. Even-MIF (Δ 200 Hg) and mass-dependent fractionation (MDF) (δ 202 Hg) of the Hg isotopes exhibited slight decrease with time, whereas odd-MIF did not show any clear trend. These results suggest a close link between the long-term evolution of GEM isotopic composition in the air and the isotopic composition of bioaccumulated Hg altered by mass-dependent fraction in the spruce shoots. Highlights: The shoots serve as passive samplers for airborne pollutants. Hg isotopic compositions of one-year-old spruce shoots were measured using CV-MC-ICP-MS. Δ 199 Hg and Δ 201 Hg did not significantly change during the study period. Δ 200 Hg and δ 202 Hg exhibited slight decreasing trends over time. Such decreases may be attributed to changes in the global and local Hg emissions.